(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2011)
This research is based on the realization of a model to determine the factors in the two-sector related industries and construction steel, in economic terms, mathematical and econometric Venezuela to generate economic growth. Being a framed research in the field of factual sciences, as a feasible project. Procedurally, the work was done from the application of accepted methodology for the econometric modeling allowed the realization of a production function is inspired by the Cobb-Douglas functional, involving those variables as their coefficients, signs statistically meaningful and fulfilling the properties of this function could be part of the model. In developing the design work resulted in a restricted model inspired the production function of Cobb-Douglas explains 93% of steel production in terms of capital and labor in construction. Conclusions and recommendations are proposed with theoretical and practical applications to guide policy decisions in public and private virtue of the existence of diminishing returns to scale in Venezuela among the sectors under study. Finally simulations are conducted based on two methods of prediction.